Spatial structure of the reserve territories of the North Caucasus - A. G. Krokhmal (Юг России: экология, развитие, 2015)
Spatial accommodation and categories of the Northern Caucasus restricted natural territories are analyzed (preserves, national parks, nature reserves and the restricted ecological-spa region of the Caucasus Mineral Waters.